ESCLEROFILIZACION DEL PAISAJE MEDITERRÁNEO - Corcuera, Leyre; Morales, Fermín; Gil-Pelegrín, Eustaquio (IV Congreso Forestal Español, 2005)
La encina es una especie con una amplitud bioclimática muy grande ya que aparece en los bioclimas semiáridos, subhúmedos, húmedos y perhúmedos (sensu Ememberg) de la Península Ibérica. En las variantes frías del bioclima húmedo y perhúmedo Quercus ilex ballota compite con los robles deciduos, Quercus faginea y Quercus pyrenaica, ocupando las crestas de las montañas donde las condiciones geopedológicas no son adecuadas para el establecimiento de los robles deciduos. En la región mediterránea el cambio climático global reciente se ha reflejado en un incremento de la aridez y calidez, que tiende a acentuarse en el futuro. A largo plazo, esto podría afectar al funcionamiento y la estructura de los ecosistemas mediterráneos, provocando la sustitución de especies menos resistentes a la sequía o afectando a las poblaciones en localidades subóptimas o en el límite biogeográfico de su distribución. Se estudió el efecto de los dos estreses climáticos propuestos por Mitrakos: el estrés hídrico estival y el estrés por frío invernal en el crecimiento de la esclerófila perennifolia Quercus ilex ballota. Para ello se analizó el efecto de la sequía en el crecimiento primario y secundario de las especies concurrentes Quercus faginea y Quercus ilex ballota y el efecto de las bajas temperaturas y alta insolación en el aparato fotosintético de Quercus ilex ballota en un clima mediterráneo continental.
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: cambio climático; cambios en el paisaje; carácter perennifolio/caducifolio; competencia interespecífica; Quercus spp

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp